Use of cannabis among 139 cluster headache sufferers. (February 2013) - Leroux, Elizabeth; Taifas, Irina; Valade, Dominique; Donnet, Anne; Chagnon, Miguel; Ducros, Anne
Aims: A case report suggested the efficacy of cannabis to treat cluster headache (CH) attacks. Our aims were to study the frequency of cannabis use in CH patients, and the reported effects on attacks. Methods: A total of 139 patients with CH attending two French headache centers filled out questionnaires. Results: Sixty-three of the 139 patients (45.3%) had a history of cannabis use. As compared to nonusers, cannabis users were more likely to be younger ( p  < 0.001), male ( p  = 0.002) and tobacco smokers ( p  < 0.001). Among the 27 patients (19.4% of the total cohort) who had tried cannabis to treat CH attacks, 25.9% reported some efficacy, 51.8% variable or uncertain effects, and 22.3% negative effects. Conclusions: Cannabis use is very frequent in CH patients, but its efficacy for the treatment of the attacks is limited. Less than one third of self-reported users mention a relief of their attacks following inhalation. Cannabis should not be recommended for CH unless controlled trials with synthetic selective cannabinoids show a more convincing therapeutic benefit.